A biophysical model of S. aurita early life history in the northern Gulf of Guinea. (February 2017) - Koné, Vamara; Lett, Christophe; Penven, Pierrick; Bourlès, Bernard; Djakouré, Sandrine
Highlights: A biophysical model of S. aurita early life history in the northern Gulf of Guinea is proposed. The physical features are the main processes determining larval drift pathways and retention areas. The role played by cyclonic and anti-cyclonic eddies in coastal retention is emphasized. Two most favorable spawning periods during the minor and the major upwelling are simulated. Abstract: S. aurita is the most abundant small pelagic fish in the northern Gulf of Guinea. Its reproduction and recruitment depend crucially on environmental conditions. We developed a biophysical model of S. aurita early life history by coupling offline an individual-based model with the regional oceanic modeling system (ROMS). We used this model to investigate the main factors driving variability in eggs and larval dispersal and survival in the northern Gulf of Guinea. Precisely, individuals were released from different spawning areas along the coast and tracked for a period of 28 days corresponding to their planktonic phase. Individuals that remained in the coastal recruitment areas at an age more than 7 days, at which they can supposedly actively retain themselves in a favorable area, were considered as recruited. Simulation results show the importance of the spawning areas around Cape Palmas and Cape Three Points where cyclonic eddies trap eggs and larvae along the coast, preventing their advection offshore by the Guinea Current. The spawning period also plays a key role in the recruitment success, with highest coastal retention obtained during the major upwelling period (July–September). We find that a second retention peak can occur during the minor upwelling period (February–March) when larval mortality due to temperature is included in the model. These results are in general agreement with knowledge of S. aurita reproduction in the northern Gulf of Guinea.